2006
DOI: 10.1021/ja061827h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electronic Polarization on Charge-Transport Parameters in Molecular Organic Semiconductors

Abstract: Theoretical investigations of charge transport in organic materials are generally based on the "energy splitting in dimer" method and routinely assume that the transport parameters (site energies and transfer integrals) determined from monomer and dimer calculations can be reliably used to describe extended systems. Here, we demonstrate that this transferability can fail even in molecular crystals with weak van der Waals intermolecular interactions, due to the substantial (but often ignored) impact of polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
781
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 794 publications
(816 citation statements)
references
References 38 publications
19
781
1
4
Order By: Relevance
“…The constrained DFT approach 19 minimizes errors that occur due to neglect of polarization in the energy splitting in the dimer method 37 by assigning charge to a single molecule within the pair when calculating the wavefunction. Moreover, Bredas, et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The constrained DFT approach 19 minimizes errors that occur due to neglect of polarization in the energy splitting in the dimer method 37 by assigning charge to a single molecule within the pair when calculating the wavefunction. Moreover, Bredas, et.…”
Section: Discussionmentioning
confidence: 99%
“…al., have shown that the principal error introduced by considering the dimer only, rather than the complete crystals, is in the difference in site energies while the transfer integral is nearly the same for the dimer and a larger system that takes even more molecules into consideration. 37 The The hole coupling and transfer rates between CPB, CTB, and DBP molecules were theoretically estimated as described in the Experimental Methods section, and are given in Table II. Our initial approach was to base our calculations on each donor dimer in the gas phase, with the dimer coordinates taken from the reported crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer integrals, ‫ݐ‬ , for molecular dimers selected from the crystal structures were evaluated using a fragment orbital approach in combination with a basis set orthogonalization procedure at the B3LYP/cc-pVDZ level. 32,33 For the long-range corrected hybrid ωB97 functional, 29 the optimal range-separation parameter ω (i.e., the ω value minimizing the many-electron self-interaction error) was determined following a non-empirical IP-tuning procedure, 34 where the difference between the highest occupied molecular orbital (HOMO) eigenvalue and the computed vertical ionization potential was minimized through the relation:…”
Section: Methodsmentioning
confidence: 99%
“…where H is the system Kohn-Sham Hamiltonian of the dimer system, and W i(j) means the monomer HOMOs (for hole transport) or LUMOs (for electron transport) with Löwdin's symmetric transformation, which can be used as the orthogonal basis set for calculation [61]. Then the intermolecular electronic coupling V ij can be written as…”
Section: Theory and Computational Methodsmentioning
confidence: 99%